Revision of the South American species of Hagenulopsis Ulmer and Askola Peters (Ephemeroptera: Leptophlebiidae) with description of six new species - Domínguez, Eduardo; Molineri, Carlos; Mariano, Rodolfo (Zootaxa, 2009)
The South American species of the genera Askola and Hagenulopsis are revised. Three new species of Askola from Brazil are described based on male imagos. Askola emmerichi sp. nov. and A. paprockii sp. nov. present spotted wings, but differ in general coloration and details of genitalia; Askola cipoensis sp. nov. is easily distinguished because the male eyes being widely separated on meson of head. Three new species of Hagenulopsis are also described: H. lipeo (from Argentina and Bolivia) and H. zunigae (from Colombia), both described from imagos and nymphs, can be recognized by details of coloration and male genitalia. H. esmeralda sp. nov. from Ecuador, described from imagos, shows a distinct male genitalia and translucent male abdomen. A key to species for the the male and female imagos of Askola and Hagenulopsis species is provided.